Data interpolation using rational cubic Ball spline with three parameters - Karim, S.A.A. (American Institute of Physics Inc., 2016)
Data interpolation is an important task for scientific visualization. This research introduces new rational cubic Ball spline scheme with three parameters. The rational cubic Ball will be used for data interpolation with or without true derivative values. Error estimation show that the proposed scheme works well and is a very good interpolant to approximate the function. All graphical examples are presented by using Mathematica software. Â© 2016 Author(s).